PENGARUH CITRA MEREK, PERSEPSI HARGA, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI HOTEL WYNDHAM CASABLANCA JAKARTA - Fikry Aji Prasetyo (Panorama Nusantara, 2021)
The purpose of this research is to determine the effect of Brand Image, Price Perception, and Service Quality partially and simultaneously on Customer Satisfaction. The population in this study are customers of Wyndham Hotel Casablanca Jakarta. The sample used in this study was 100 people bye purposive method. Data were analyzed by descriptive and quantitative. The regression analysis started with the classical assumption test (Normality, Multicolinearity, Heterocedasticity, and Linearity Test) afterward by multiple linear regression analysis. The model determined by the hypothesis testing applied F test, t test, correlation test, and the coefficient of determination (R2). The results showed that Brand Image has a significant effect on Customer Satisfaction, Price Perception has a significant effect on Customer Satisfaction, and Service Quality has a significant effect on Customer Satisfaction, where all variables simultaneously have a positive effect on Customer Satisfaction at Wyndham Hotel Casablanca Jakarta